Effects of parental input quality in child heritage language acquisition. Issue 4 (15th July 2020) - DASKALAKI, Evangelia; BLOM, Elma; CHONDROGIANNI, Vasiliki; PARADIS, Johanne
Abstract: This study investigates the role of parental input quality on the acquisition of Greek as a heritage language in Western Canada. Focusing on subject use, we tested four groups of Greek speakers: monolingual children, heritage children, and the parents of each one of those groups. Participants completed an elicited production task designed to elicit subject placement in wide focus and embedded interrogative contexts, where postverbal subjects are preferred/required in the monolingual variety. Results gave rise to two main conclusions: first, the parental input received by heritage children may be qualitatively different from the parental input received by monolingual children, in that it contains a higher rate of deviant preverbal subjects. Second, parental input quality in addition to quantity may affect the outcome of heritage language acquisition, in that children producing a higher rate of preverbal subjects had parents whose Greek input was not only quantitatively reduced, but also richer in preverbal subjects.